The disabled child physical activity role in the formation of trust in structure of the family’s social capital - M.V. Kurnikova (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2021)
Background. The phenomenon of trust is considered as a necessary element and resource for the genesis of the social capital of a family with a disabled child and his transformation in the social space of physical culture and sports. The purpose of the work is to reveal the influence of regular physical activity of a disabled child on the formation of trusting relationships in family ecosystem. Materials and methods. Families with a disabled child, practicing and not practicing regular physical activity (parents and siblings over 14 years old, n = 218 and n = 267, respectively) and family members with a healthy child (n = 374), were interviewed by questionnaire. The preferential fields of communication of the individual for forming social connections and receiving news information, the individual’s attitude to social institutions in a difficult life situation are defined as indicators of trust. Results. The presence of a disabled child in the family reduces the level of trusting verbal interaction among all family members, concentrating on communication in local communities and social networks. Mothers tend to rely on government structures and institutions, while fathers rely on their own strength in solving their family and life problems. Due to the regular and structured physical activity of a disabled child, his parents and siblings are motivated to change their lifestyle against the background of active interaction with the space of physical culture and sports. Fathers show positive dynamics of increasing trust in family ties, friends, public and volunteer organizations, and mothers show an increase in selfconfidence against the background of declining expectations of help from government agencies. Conclusions. Physical culture and sports can be considered as a means of transforming social capital through the genesis of trust by including a disabled child in regular sports or other forms of recreational physical activity in the context of cooperation between parents of disabled children and physical culture and sports organizations.